Teoria i praktyka międzynarodowej współpracy gospodarczej krajów RWPG - Najlepszy, Eugeniusz (Wydział Prawa i Administracji UAM, 1983)
The task of the article is a comparison of theoretical findings of the conception of the international economic cooperation of the CMEA member states with the premises of their economic policies in this scope and with the previous course of integrational processes in the CMEA group. In the first part of the study, three basic theoretical concepts of economic cooperation are presented which can be related to differing views of economists on the part played by planning and international market in the socialist economy. In the second part of the study a system of the international economic cooperation adopted in the premises of the economic policies of the CMEA member states is analyzed. The author's attention is focused mainly on those elements of the international cooperation system which are compromising opposing pursuits of the particular member states of securing themselves most favorable conditions for balancing necessary means with needs stated autonomously in the national plans of economic developement. The third part of the study is devoted to the analysis of features of functioning of the present system of international cooperation of the CMEA states. The actual distribution of competence and roles in the system of relations between various levels of domestic and international institutions and organizations are characterized. The scope of implementation of resolutions and recommendations of the CMEA on the developement of the international specialization and productional cooperation is evaluated. The excessive build up of the consulting and negociating activities almost on all the levels of economic organizations of the member states and of the CMEA organs is also indicated. The identification and analysis of structure of interdependence of economic interests in the sphere of realization of international economic cooperation in the CMEA are performed. Particularly, following groups of interests can be singled out: Party and government governing bodies, central economic administration, productional and trade enterprises, international organs of the CMEA. In the final remarks factors diminishing the ability to control a mechanism of the international cooperation are presented, this can well account for the lack of developement in real integrational ties and related organizational structures in the system of cooperation of the CMEA states.
Theory and practice of the international economic cooperation of the CMEA states